Baking performance of palm diacylgiycerol bakery fats and sensory evaluation of baked products - Cheong, Ling Zhi; Tan, Chin Ping; Long, Kamariah; Idris, Nor Aini; Yusof, Mohd. Suria Affandi; Lai, Oi Ming (Wiley - V C H Verlag GmbH & Co. KGaA, 2011)
Baking performance of palm diacylglycerol (PDG)-enriched fats was evaluated and compared with that of commercial bakery fats. PDG-enriched shortenings were found to produce cakes with significantly (p<0.05) higher mean values for specific volume than that produced from commercial shortening. As for PDG-enriched margarines, cookies prepared from PDG-enriched margarines were found to have reduction in cookies spread as compared to that of commercial shortening. Nevertheless, this reduction was not statistically significant. Sensory evaluation of the baked products was also conducted. Both trained and untrained panelists rated cakes prepared from PDG-enriched shortenings as having higher moistness, softer, and airier texture than that of commercial shortening. This is in agreement with findings from principal component analysis (PCA). As for cookies, both trained and untrained panelists rated cookies prepared from PDG-enriched margarines as having softer texture and compactness compared to that prepared from commercial margarine.